Scientific production on penitentiary health in Brazilian nursing - Mayara Lima Barbosa; Alcides Viana de Lima Neto; Cecília Olívia Paraguai de Oliveira Saraiva; Manacés dos Santos Bezerril; Gabriela Maria Cavalcanti Costa; Viviane Euzébia Pereira Santos (Universidade Federal de Santa Maria, 2019)
Objective: To characterize the studies published in the Center for Studies and Research in Nursing that address the theme of penitentiary health. Method: This is a bibliographic search, which was searched in the CEPEn database, in the catalogs available electronically - corresponding to Volume XIX (2001) to XXXIV (2016). Results: The analysis was performed on the 9514 titles in the database, among which nine (0.095%) dissertations and theses were developed on the subject and make up the final sample. Of these, only one study related nursing and penitentiary health and three highlighted implications for the profession. Conclusion: It is clear that fostering discussion on the topic represents a breakthrough and is essential to fill the gaps in health care delivery in this scenario.